1970
DOI: 10.1017/s0022149x00021714
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Some Species of Digenea with the Marine Prosobranch Littorina littorea (L.) I. The Occurrence of Larval Digenea in L, littorea on the North Yorkshire Coast

Abstract: 1. 8515 specimens of the common periwinkle, Littorina littorea (L.), from four localities on the North Yorkshire coast were examined for larval Digenea during 1966 and 1907. Four species were found, namely Cryptocotyle lingua (Creplin, 1825), Himasthla leptosoma (Creplin, 1829), Cercaria lebouri Stunkard, 1932 and Cercaria A, the incidence of infection with which correlated with the presence of sea bird and wader final hosts.2. 5878 of all L. littorea examined were from one locality of relatively high incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
2
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 13 publications
2
54
2
2
Order By: Relevance
“…There were variations in incidence of infection among both the farm and control sites, and factors such as inter-tidal environmental conditions and differences In resistance among periwinkle strains may influence the abundance of C. lingua in snail hosts (Robson & Williams 1970). There is, however, no reason to believe that such factors would have led to the higher levels of infection recorded in periwinkle population~ collected adjacent to the fish farms in the current study.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…There were variations in incidence of infection among both the farm and control sites, and factors such as inter-tidal environmental conditions and differences In resistance among periwinkle strains may influence the abundance of C. lingua in snail hosts (Robson & Williams 1970). There is, however, no reason to believe that such factors would have led to the higher levels of infection recorded in periwinkle population~ collected adjacent to the fish farms in the current study.…”
Section: Discussioncontrasting
confidence: 50%
“…Several authors have concluded that the presence and behaviour of piscivorous birds have the most decisive impact upon the incidence of infection of Cryptocotyle lingua in periwinkle populations (Hoff 1941, Sindermann & Farrin 1962, Robson & Williams 1970, Hughes & Answer 1982, Irwin 1983, Matthews et al 1985, Lauckner 1987. Although not quantified, quite large numbers of birds were observed in the vicinity of the farms during the current investigation.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Although seasonal variation in the prevalence of parasitic infections in intertidal snails is common (L. littorea: Hughes and Answer 1982, Lauckner 1987, Pohley 1976, Robson and Williams 1971, Sindermann and Farrin 1962Hydrobia spp: Field andIrwin 1999, Kube et al 2002), we sampled during summer because a higher prevalence of infection occurs during summer months compared to winter months. Poulin and Mouritson (2003) attribute low prevalence of infection during winter months to ambient water temperatures.…”
Section: Discussionmentioning
confidence: 99%